Optimasi Algoritma K-Nearest Neighbors Menggunakan Teknik Bayesian Optimization Untuk Klasifikasi Diabetes - Sowabi, Nur Kholis; Widiastuti, Nur Aeni; Maori, Nadia Annisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Diabetes is one of the chronic diseases that affects millions of people worldwide. Early diagnosis is crucial to prevent long-term complications, but the main challenges lie in the complexity of medical data and selecting optimal parameters for classification algorithms. This research aims to optimize the K-Nearest Neighbors (KNN) algorithm using Bayesian Optimization to improve accuracy in diabetes classification. The dataset used is the